2021
DOI: 10.1039/d0sm01896a
|View full text |Cite
|
Sign up to set email alerts
|

Towards designing globular antimicrobial peptide mimics: role of polar functional groups in biomimetic ternary antimicrobial polymers

Abstract: Using atomistic molecular dynamics simulations, we study the interaction of ternary methacrylate polymers, composed of charged cationic, hydrophobic and neutral polar groups, with model bacterial membrane.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…Simulations of synthetic antimicrobial polymers performed in the presence of a representative lipid bilayer have increased understanding of the conformational changes to polymer chain that occur during the interaction with the bacterial membrane. [ 23n,79d,98,133 ] More recently, they have enabled the stabilization of proteins by random copolymers mediated by interactions between functionalities statistically distributed along the polymer chain and the corresponding spatially distributed patches on the protein surface. [ 42a,134 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations of synthetic antimicrobial polymers performed in the presence of a representative lipid bilayer have increased understanding of the conformational changes to polymer chain that occur during the interaction with the bacterial membrane. [ 23n,79d,98,133 ] More recently, they have enabled the stabilization of proteins by random copolymers mediated by interactions between functionalities statistically distributed along the polymer chain and the corresponding spatially distributed patches on the protein surface. [ 42a,134 ]…”
Section: Discussionmentioning
confidence: 99%
“…[97d] Besides improving biocompatibility, a very recent molecular dynamics simulation study by Rani et al suggested that ternary random copolymers (as exemplified via a polymethacrylate system) adopt a more folded conformation and can penetrate deeper into bacteria membranes even though the ternary copoly mers lack the amphiphilic conformations typically found in binary copolymers that contain only cationic and hydrophobic moieties. [98] This is an interesting finding and may seem counterintuitive at first considering that a hydrophilic functionality would allow the polymer to penetrate better across the hydrophobic tails of a bacteria membrane. Taken together, these studies strengthen the case for including polar uncharged groups in the design of antimicrobial polymers-bearing in mind that most natural AMPs are also made up of polar uncharged serine and glycine amino acids.…”
Section: Incorporation Of Neutral Polar Groupsmentioning
confidence: 99%
“…The conformation of SS-free HAV-2B peptide is such that it acquires a strong facially amphipihilic character upon segregation of hydrophobic and hydrophilic residues. Different membrane-active agents including antimicrobial peptides (Leontiadou et al 2006 ; Mondal et al 2010 ; Vanni et al 2014 ), polymers (Baul et al 2014 ; Baul & Vemparala, 2015 , 2017 ; Palermo et al 2012 , 2013 ; Rahman et al 2018 ; Rani et al 2021 ) and other membrane-active molecules (Devanand et al 2019 ; Polley & Vemparala, 2013 ; Vemparala et al 2006 ) are known to acquire such amphipihilic conformations upon partitioning into cellular membranes. However, in SS11-47 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The conformation of SS-free HAV-2B peptide is such that it acquires a strong facially amphipihilic character upon segregation of hydrophobic and hydrophilic residues. Different membrane active agents including antimicrobial peptides [55,62,63], polymers [58,[64][65][66][67][68][69] and other membrane active molecules [70][71][72] are known to acquire such amphipihilic conformations upon partitioning into cellular membranes. However, in SS11-47 (Fig 6C ) and SS11-52 (Fig 6D ) states, the hydrophobic accessible surface area is limited resulting in mitigation of peptide partitioning.…”
Section: Discussionmentioning
confidence: 99%